LITTER DECOMPOSITION RATES IN RANGELANDS AND THEIR IMPACT ON PLANT PHYSIOLOGICAL CHARACTERISTICS - Khushbekova Muhayyo Sobirjon qizi,; Oxunova Surayyo Sobirjonovna,; Abdumuratova Dinora Akmal qizi,; Djurabayeva Farannoz Oybekovna,; Ravshanov Xudoyberdi Ravshanovich, (TADQIQOTLAR, 2026)
Abstract The degradation of rangelands is widely recognised as a significant global issue. It  is  crucial  to  assess  the  resilience  of  rangeland  ecosystems  by  evaluating decomposition rates and plant ecophysiological responses. This study used a Tea Bag Index  (TBI)  methodology  to  assess  soil  decomposition,  as  well  as  enzymology techniques  to  determine  chlorophyll  content.  The  findings  showed  that  soil decomposition  rates  increased  with  distance  from  watering  wells.  However,  a contrasting trend was observed in the change in chlorophyll a content of Artemisia diffusa. In conclusion, further investigation is required across the entire rangeland area.